2010
DOI: 10.1002/tax.591021
|View full text |Cite
|
Sign up to set email alerts
|

Disintegrating Portulacaceae: A new familial classification of the suborder Portulacineae (Caryophyllales) based on molecular and morphological data

Abstract: Traditional classifications of the suborder Portulacineae recognize six families: Basellaceae, Cactaceae, Didiereaceae, Halophytaceae, Hectorellaceae, and Portulacaceae. However, phylogenetic analyses based on molecular sequence data indicate that the traditional family Portulacaceae is paraphyletic and consists of three distinct lineages that also include Cactaceae, Didiereaceae, and Hectorellaceae. We use sequence data from the chloroplast genes matK and ndhF representing 64 species of Portulacineae and outg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(81 citation statements)
references
References 54 publications
3
72
1
2
Order By: Relevance
“…(Tropicos 2010) should possibly be resurrected for H. spergulacea . Molluginaceae are highly supported as the sister group of the Portulacineae clade (Nyffeler et al 2008; Nyffeler and Eggli, 2010) and contain the genera Mollugo , Adenogramma , Coelanthum , Glinus , Glischtrothamnus , Pharnaceum , Polpoda , Psammotropha , and Suessenguthiella , and H. spergulacea (Figs. 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…(Tropicos 2010) should possibly be resurrected for H. spergulacea . Molluginaceae are highly supported as the sister group of the Portulacineae clade (Nyffeler et al 2008; Nyffeler and Eggli, 2010) and contain the genera Mollugo , Adenogramma , Coelanthum , Glinus , Glischtrothamnus , Pharnaceum , Polpoda , Psammotropha , and Suessenguthiella , and H. spergulacea (Figs. 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Note that throughout we follow the taxonomy of the New Cactus Lexicon (Hunt, 2006), using only species names accepted in this source. The taxonomic distribution of samples represented in our final matrix is summarised in Table 2. Recent studies have shown the Cactaceae to be a wellsupported monophyletic group most closely related to family Anacampserotaceae (formerly tribe Anacampseroteae; Nyffeler and Eggli, 2010) and the genera Portulaca and Talinum of the family Portulacaceae (Nyffeler, 2007). We include sequences previously published by Nyffeler (2002) to represent these groups, Grahamia bracteata of the Anacampserotaceae, Portulaca oleracea, and Talinum paniculatum.…”
Section: Methodsmentioning
confidence: 99%
“…In Portulacaceae, which has 29 genera as traditionally circumscribed (Eggli, 2002; but see Nyffeler and Eggli, 2010 for an alternative circumscription), only Portulaca is known to have C 4 species. Previous suggestions that some species of Anacampseros and Grahamia may be C 4 are not supported by a recent study (Guralnick et al , 2008), which indicates the occurrence of Crassulacean acid metabolism (CAM) rather than C 4 photosynthesis in these genera.…”
Section: Introductionmentioning
confidence: 99%